Penerapan Pemasaran Digital Sebagai Media Promosi - Sussanti Sussanti; Veronica Krisni Damayanti; Mulyadi Amin (Pusat Riset dan Inovasi Nasional, 2024)
Digital marketing as a promotional strategy emerged as a response to developments in information technology. The use of digital marketing is not only limited to new companies or start-ups, but is also applied by companies that have been around for a long time. PT. XYZ, which functions as a motor vehicle distributor and retailer, is also required to adopt digital marketing even though it already has a strong brand from its parent company. In this research, which uses a case study of PT. XYZ, data obtained through observation and interviews. The research results show that PT. XYZ uses three media in implementing digital marketing, namely websites, social media and applications. Of the three media, social media such as Instagram and Facebook show the best results, because both are used to provide information and build engagement with consumers.